A co-based spinel structure-based active material, a preparation method thereof and application thereof in a no gas sensor
Patent Information
- Application Number
- CN202610510852.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-17
- Publication Date
- 2026-09-22
AI Technical Summary
此类传感器无需外加电源,具有在室温条件下自功能运行的能力,然而,针对NO检测的燃料电池型气体传感器鲜有报道
(1)本方案提供的一种基于Co基尖晶石结构的活性材料的制备方法,通过调控金属硝酸盐前驱体与硝酸钴的比例,进而调控尖晶石结构中A位阳离子种类及含量实现电子结构调节Co基尖晶石材料。
Smart Images

Figure CN122787019A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of NO gas sensor technology, specifically to an active material based on a Co-based spinel structure, its preparation method, and its application in NO gas sensors. Background Technology
[0002] Nitric oxide (NO) is a gaseous pollutant produced during the combustion of fossil fuels. It plays a significant role in the formation of acid rain and photochemical smog. Furthermore, NO is closely associated with respiratory diseases and is widely considered a biomarker for conditions such as asthma. Therefore, achieving accurate detection of low concentrations of NO is of great importance for environmental monitoring and respiratory health diagnosis.
[0003] Currently, NO detection technologies mainly include semiconductor gas sensors, electrochemical sensors, optical detection methods, and gas chromatography. Semiconductor metal oxide sensors, particularly those in the semiconductor gas sensor category, offer advantages such as simple structure and low cost; however, they typically require high operating temperatures, leading to high energy consumption, and suffer from insufficient selectivity in monitoring low-concentration NO. Traditional electrochemical sensors, while capable of detection at lower temperatures, usually rely on external power supplies, hindering miniaturization and portability. Optical detection and gas / liquid chromatography offer high detection accuracy, but the systems are complex, require specialized personnel for operation, and are costly.
[0004] Fuel cell gas sensors are devices that use electrode materials to catalyze the oxidation of a target gas, directly converting chemical energy into an electrical signal output. These sensors require no external power supply and are capable of self-operating at room temperature. However, there are few reports on fuel cell gas sensors for NO detection.
[0005] Therefore, this application provides a novel fuel cell-type gas sensor for NO detection. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides an active material based on a Co-based spinel structure, its preparation method, and its application in a NO gas sensor, thus solving the problems mentioned in the background section.
[0007] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a method for preparing an active material based on a Co-based spinel structure is provided, comprising the following steps: S1. Dissolve the metal nitrate precursor and cobalt nitrate in a mixed solvent to obtain solution A, wherein the metal element in the metal nitrate precursor is selected from any one of Al, Fe, Mn, Ga, Cu, Ni, and Zn; S2. Dissolve 2-methylimidazole in methanol to obtain solution B; S3. Under stirring conditions, solution B is added to solution A and mixed evenly, then subjected to a hydrothermal reaction, dried, and calcined to obtain the active material.
[0008] Preferably, in step S1, the metal element in the metal nitrate precursor is selected from Ni or Zn.
[0009] Preferably, in step S1, the molar ratio of the metal nitrate precursor to cobalt nitrate is 0.2 to 1:1, wherein the metal nitrate precursor is measured in molar amounts of metal elements, and the cobalt nitrate is measured in molar amounts of cobalt elements. The mixed solvent includes water and methanol, and the volume ratio of water to methanol is 2:1.
[0010] Preferably, in step S2, the molar ratio of 2-methylimidazole to cobalt nitrate is 3~6:1, wherein the cobalt nitrate is expressed in molar amounts of cobalt element.
[0011] Preferably, in step S3, the temperature of the hydrothermal reaction is 120~140℃ and the time is 3~6 h; The drying temperature is 60~80℃; The calcination conditions are as follows: heating to 300~600℃ at a heating rate of 2℃ / min, and holding at that temperature for 1~2 hours.
[0012] According to a second aspect of the present invention, an active material obtained by the above preparation method is provided, the active material having the molecular formula M x Co 3-x O4, where x = 0.2~1, and M is selected from any one of Al, Fe, Mn, Ga, Cu, Ni, and Zn; The active material has a spinel structure with an interwoven nanosheet structure on its surface.
[0013] More preferably, the molecular formula of the active material is Zn. x Co 3-x O4, where x = 0.2, 0.4, 0.6, 0.8.
[0014] More preferably, the molecular formula of the active material is Zn. 0.4 Co 2.6 O4.
[0015] According to a third aspect of the present invention, an application of an active material in an NO gas sensor is provided, wherein the NO gas sensor is prepared by the following method: A. The Nafion membrane was placed in a 0.5M sulfuric acid solution and heated at 80°C for 1 hour to obtain a protonated Nafion membrane. B. Disperse 5 mg of active material in a mixed system containing 460 μL isopropanol and 40 μL Nafion solution, and sonicate under ice bath conditions to obtain a dispersion. C. The dispersion is drop-coated onto two carbon paper substrates, dried, and then 20 μL of Nafion solution is dropped onto the surface of each coated carbon paper, and the paper is dried further to obtain coated carbon paper. D. The protonated Nafion membrane is sandwiched between two pieces of carbon paper coated with active material, and after hot pressing, a membrane electrode assembly is formed. Then, a copper electrode is connected and sealed to obtain the NO gas sensor.
[0016] This invention provides an active material based on a Co-based spinel structure, its preparation method, and its application in a NO gas sensor. It offers the following advantages: (1) This solution provides a method for preparing active materials based on Co-based spinel structure. By adjusting the ratio of metal nitrate precursor to cobalt nitrate, the type and content of A-site cations in the spinel structure can be adjusted to achieve electronic structure regulation of Co-based spinel materials.
[0017] (2) This solution provides an active material based on a Co-based spinel structure, which optimizes the valence distribution of Co ions at the B site and the state of active sites through the regulation of A-site cations, thereby enabling the Co ions at the B site to... 3+ It becomes the active center that mainly participates in NO adsorption and electrocatalytic reaction, improving the adsorption capacity of NO molecules and the efficiency of catalytic reaction, thereby enhancing the sensitivity and room temperature detection capability of the active material in fuel cell-type NO sensors, achieving NO detection at the ppb level under certain conditions. Attached Figure Description
[0018] Figure 1 A schematic diagram of the structure of the NO gas sensor made from the active material used in the invention; Figure 2 The images show the XRD patterns of the active materials prepared in Examples 1-7 and Comparative Example 1 of this invention, where (a) is the XRD pattern of AlCo2O4, (b) is the XRD pattern of FeCo2O4, (c) is the XRD pattern of MnCo2O4, (d) is the XRD pattern of CuCo2O4, (e) is the XRD pattern of GaCo2O4, (f) is the XRD pattern of ZnCo2O4, (g) is the XRD pattern of NiCo2O4, and (h) is the XRD pattern of Co3O4. Figure 3The images shown are SEM images of the active materials prepared in Examples 1-7 and Comparative Example 1 of this invention, wherein (a) is an SEM image of AlCo2O4, (b) is an SEM image of FeCo2O4, (c) is an SEM image of MnCo2O4, (d) is an SEM image of CuCo2O4, (e) is an SEM image of GaCo2O4, (f) is an SEM image of ZnCo2O4, (g) is an SEM image of NiCo2O4, and (h) is an SEM image of Co3O4. Figure 4 The following is a statistical analysis of the response of the active materials prepared in Examples 1-7 and Comparative Example 1 to various gases at 50 ppm in a NO gas sensor. Among them, (a) is the response diagram of AlCo2O4, (b) is the response diagram of FeCo2O4, (c) is the response diagram of MnCo2O4, (d) is the response diagram of GaCo2O4, (e) is the response diagram of CuCo2O4, (f) is the response diagram of Co3O4, (g) is the response diagram of ZnCo2O4, and (h) is the response diagram of NiCo2O4. Figure 5 The XRD patterns are of the active materials prepared in Examples 7-11 of this invention. Figure 6 The response statistics of the active materials prepared in Examples 7-11 of this invention to various gases at 50 ppm in an NO gas sensor are presented. Figure 7 The figures show the dynamic response curves of the active materials prepared in Examples 7-11 of this invention to NO gas sensors under different NO concentrations. (a) is the response curve, and (b) is the linear relationship between the response values of different NO gas sensors and the NO concentration. Figure 8 The active material prepared in Example 9 of this invention is used in an NO gas sensor to respond to low concentrations of NO. Detailed Implementation
[0019] To better illustrate the content of this invention, the following description is provided in conjunction with specific embodiments.
[0020] This invention provides a method for preparing an active material based on a Co-based spinel structure, comprising the following steps: Step 1: Dissolve the metal nitrate precursor and cobalt nitrate in a mixed solvent and obtain solvent A under vigorous stirring. The metal element in the metal nitrate precursor is selected from any one of Al, Fe, Mn, Ga, Cu, Ni, and Zn. Step 2: Dissolve 2-methylimidazole in methanol to obtain solution B; Step 3: Under stirring conditions, add solution B to solution A to obtain a mixed solution. Then, transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene for hydrothermal reaction. After the reaction is completed, collect the precipitate, wash it twice with deionized water, then wash it twice with ethanol, and then dry it in an oven. The dried precipitate is calcined in a muffle furnace to obtain the active material.
[0021] The molecular formula of the active material prepared by this invention is M x Co 3-x O4, where x = 0.2~1, and M is selected from any one of Al, Fe, Mn, Ga, Cu, Ni, and Zn; The active material has a spinel structure with an interwoven nanosheet structure on its surface.
[0022] The active materials prepared according to the following embodiments and comparative examples of the present invention are applied to NO gas sensors. The specific preparation and application processes are as follows: A. First, the Nafion membrane was placed in a 5% hydrogen peroxide solution and heated to 80°C for 1 hour to remove organic impurities from the membrane. Then, it was washed with deionized water and heated in deionized water at 80°C for 1 hour to remove excess hydrogen peroxide. Next, the Nafion membrane was placed in a 0.5M sulfuric acid solution and heated at 80°C for 1 hour to replenish protons. Finally, it was heated in deionized water at 80°C for 1 hour to remove excess sulfuric acid, thus obtaining a protonated Nafion membrane. B. Disperse 5 mg of active material in a mixed system containing 460 μL isopropanol and 40 μL Nafion solution, and sonicate under ice bath conditions to obtain a dispersion. C. The dispersion is drop-coated onto two carbon paper substrates, dried, and then 20 μL of Nafion solution is dropped onto the surface of each coated carbon paper, and the paper is dried further to obtain coated carbon paper. D. The protonated Nafion membrane is sandwiched between two sheets of carbon paper coated with active material, and after hot pressing, a membrane electrode assembly is formed. Then, a copper electrode is connected, and the assembly is sealed to obtain the NO gas sensor. The specific structure is as follows: Figure 1 As shown.
[0023] Example 1 Step 1: Dissolve 1 mmol of aluminum nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate to 400℃ in a muffle furnace at a heating rate of 2℃ / min and hold for 1 h to obtain AlCo2O4 active material.
[0024] Example 2 Step 1: Dissolve 1 mmol of ferric nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate to 400℃ in a muffle furnace at a heating rate of 2℃ / min and hold it for 1 h to obtain FeCo2O4 active material.
[0025] Example 3 Step 1: Dissolve 1 mmol of manganese nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate in a muffle furnace to 400℃ at a heating rate of 2℃ / min and hold it for 1 h to obtain the MnCo2O4 active material.
[0026] Example 4 Step 1: Dissolve 1 mmol of gallium nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate to 400℃ in a muffle furnace at a heating rate of 2℃ / min and hold it for 1 h to obtain the GaCo2O4 active material.
[0027] Example 5 Step 1: Dissolve 1 mmol of copper nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate in a muffle furnace to 300℃ at a heating rate of 2℃ / min and hold it for 1 h to obtain CuCo2O4 active material.
[0028] Example 6 Step 1: Dissolve 1 mmol of nickel nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate to 400℃ in a muffle furnace at a heating rate of 2℃ / min and hold for 1 h to obtain NiCo2O4 active material.
[0029] Example 7 Step 1: Dissolve 1 mmol of zinc nitrate and 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate to 400℃ in a muffle furnace at a heating rate of 2℃ / min and hold for 1 h to obtain ZnCo2O4 active material.
[0030] Comparative Example 1 Step 1: Dissolve 2 mmol of cobalt nitrate hexahydrate in 30 mL of mixed solvent (deionized water: methanol = 2:1) and stir vigorously to obtain solution A; Step 2: Dissolve 6 mmol of 2-methylimidazole in 6 mL of methanol to obtain solution B; Step 3: Under continuous stirring, add solution B to solution A and continue stirring for 30 min. Then transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and carry out a hydrothermal reaction at 120℃ for 3 h. After the reaction, collect the precipitate, wash it twice with deionized water and twice with ethanol, and then dry it in an oven at 60℃. Finally, heat the dried precipitate in a muffle furnace to 400℃ at a heating rate of 2℃ / min and hold it for 1 h to obtain the Co3O4 active material.
[0031] The active materials prepared in Examples 1 to 7 and Comparative Example 1 were subjected to XRD analysis, respectively. Figure 2 As shown, all results correspond perfectly with the standard PDF card, indicating that the synthesized material is a pure active material. It can also be seen that when M is Al, it occupies a mixed AB site; when M is Fe, Mn, Ga, or Cu, it occupies only the B site; and when M is Ni or Zn, it occupies only the A site.
[0032] SEM analysis was performed on the active materials prepared in Examples 1 to 7 and Comparative Example 1, respectively. Figure 3 As shown, the introduction of metal M did not cause significant morphological changes, and the prepared active material exhibited an interwoven nanosheet structure. However, the introduction of Fe caused some nanosheets to break, possibly due to the significant lattice transformation caused by Fe substitution, which altered the lattice growth kinetics and disrupted the self-assembly behavior of the nanosheet structure.
[0033] The active materials prepared in Examples 1 to 7 above were applied to a NO gas sensor, and the response statistics for various gases at 50 ppm are as follows: Figure 4As shown, the active material prepared when M is Ga, Zn, or Ni has excellent sensitivity response to NO. However, when M is Ni, other interfering gases will also affect the NO gas sensor, resulting in relatively poor selectivity. Therefore, Ga or Zn is the preferred metal for M.
[0034] Example 8 The preparation method in this embodiment is the same as that in Example 7, except that in step 1, 0.2 mmol of zinc nitrate and 2.8 mmol of cobalt nitrate hexahydrate are dissolved in 30 mL of a mixed solvent (deionized water: methanol = 2:1), and the solution is stirred vigorously to obtain solution A. Subsequent steps are the same to obtain Zn. 0.2 Co 2.8 O4 active material.
[0035] Example 9 The preparation method in this embodiment is the same as that in Example 7, except that in step 1, 0.4 mmol of zinc nitrate and 2.6 mmol of cobalt nitrate hexahydrate are dissolved in 30 mL of a mixed solvent (deionized water: methanol = 2:1), and the solution is stirred vigorously to obtain solution A. Subsequent steps are the same to obtain Zn. 0.4 Co 2.6 O4 active material.
[0036] Example 10 The preparation method in this embodiment is the same as that in Example 7, except that in step 1, 0.6 mmol of zinc nitrate and 2.4 mmol of cobalt nitrate hexahydrate are dissolved in 30 mL of a mixed solvent (deionized water: methanol = 2:1), and the solution is stirred vigorously to obtain solution A. Subsequent steps are the same to obtain Zn. 0.6 Co 2.4 O4 active material.
[0037] Example 11 The preparation method in this embodiment is the same as that in Example 7, except that in step 1, 0.8 mmol of zinc nitrate and 2.2 mmol of cobalt nitrate hexahydrate are dissolved in 30 mL of a mixed solvent (deionized water: methanol = 2:1), and the solution is stirred vigorously to obtain solution A. Subsequent steps are the same to obtain Zn. 0.8 Co 2.2 O4 active material.
[0038] The active materials prepared in Examples 7 to 11 were subjected to XRD tests, respectively. Figure 5 As shown, according to Figure 5 It can be seen that the diffraction peaks of the active materials prepared in various proportions all match the spinel structure phase well, and no impurity peaks were observed, thus successfully obtaining pure phase samples.
[0039] The active materials prepared in Examples 7 to 11 above were applied to a NO gas sensor, and the response statistics for various 50 ppm gases are as follows: Figure 6 As shown, all active materials exhibit excellent selectivity for NO, and Zn 0.4 Co 2.6 The O4 active material exhibits the highest response value, which is 66.1% and 32.0% higher than that of ZnCo2O4 and Co3O4, respectively.
[0040] The active materials prepared in Examples 7 to 11 above were used in NO gas sensors to test the dynamic response under different NO concentrations, as follows: Figure 7 As shown in Figure (a), Zn 0.4 Co 2.6 O4-active materials exhibited the highest response values; according to Figure 7 As shown in Figure (b), NO gas sensors prepared using different active materials all exhibit good linearity.
[0041] Further research on Zn 0.4 Co 2.6 The sensing performance of O4-active materials under low NO concentration conditions was studied, such as... Figure 8 As shown, Zn 0.4 Co 2.6 The O4 active material still exhibits a significant response even at a NO gas concentration of 25 ppb, indicating its high sensitivity to NO gas detection and its excellent application potential in the field of medical diagnostics.
[0042] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an active material based on a Co-based spinel structure, characterized in that: Includes the following steps: S1. Dissolve the metal nitrate precursor and cobalt nitrate in a mixed solvent to obtain solution A, wherein the metal element in the metal nitrate precursor is selected from any one of Al, Fe, Mn, Ga, Cu, Ni, and Zn; S2. Dissolve 2-methylimidazole in methanol to obtain solution B; S3. Under stirring conditions, solution B is added to solution A and mixed evenly, then subjected to a hydrothermal reaction, dried, and calcined to obtain the active material.
2. The method for preparing an active material based on a Co-based spinel structure according to claim 1, characterized in that: In step S1, the metal element in the metal nitrate precursor is selected from Ni or Zn.
3. The method for preparing an active material based on a Co-based spinel structure according to claim 1, characterized in that: In step S1, the molar ratio of the metal nitrate precursor to cobalt nitrate is 0.2 to 1:1, wherein the metal nitrate precursor is measured in molar amounts of metal elements, and the cobalt nitrate is measured in molar amounts of cobalt elements. The mixed solvent includes water and methanol, and the volume ratio of water to methanol is 2:
1.
4. The method for preparing an active material based on a Co-based spinel structure according to claim 1, characterized in that: In step S2, the molar ratio of 2-methylimidazole to cobalt nitrate is 3~6:1, wherein the cobalt nitrate is expressed in molar amounts of cobalt element.
5. The method for preparing an active material based on a Co-based spinel structure according to claim 1, characterized in that: In step S3, the hydrothermal reaction is carried out at a temperature of 120~140℃ for 3~6 hours. The drying temperature is 60~80℃; The calcination conditions are as follows: heating to 300~600℃ at a heating rate of 2-4℃ / min, and holding at that temperature for 1~2 hours.
6. An active material obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The molecular formula of the active material is M x Co 3-x O4, where x = 0.2~1, and M is selected from any one of Al, Fe, Mn, Ga, Cu, Ni, and Zn; The active material has a spinel structure with an interwoven nanosheet structure on its surface.
7. The application of an active material according to claim 6 in a NO gas sensor, characterized in that: The method for preparing the NO gas sensor is as follows: A. The Nafion membrane was placed in a 0.5M sulfuric acid solution and heated at 80°C for 1 hour to obtain a protonated Nafion membrane. B. Disperse 5 mg of active material in a mixed system containing 460 μL isopropanol and 40 μL Nafion solution, and sonicate under ice bath conditions to obtain a dispersion. C. The dispersion is drop-coated onto two carbon paper substrates, dried, and then 20 μL of Nafion solution is dropped onto the surface of each coated carbon paper, and the paper is dried further to obtain coated carbon paper. D. The protonated Nafion membrane is sandwiched between two pieces of carbon paper coated with active material, and after hot pressing, a membrane electrode assembly is formed. Then, a copper electrode is connected and sealed to obtain the NO gas sensor.